Advanced strength and conditioning an evidence-based approach - Comfort, Paul; Turner, Anthony (Anthony N.) (London New York Routledge,Taylor & Francis Group, 2018)
Becoming an effective strength and conditioning practitioner requires the development of a professional skills set and a thorough understanding of the scientific basis of best practice. Aimed at advanced students and beginning practitioners, this book explores the latest scientific evidence and applied it to exercise selection and programming choices across the full range of functional areas in strength and conditioning, from strength to power to speed and agility. With coverage of data analysis and performance feedback, both vital skills for contemporary strength and conditioning coach, this concise but sophisticated textbook is the perfect bridge from introductory study to effective professional practice. Written by experts with experience in a wide variety of sports, its chapters are enhanced by extensive illustrations and address key topics such as: fitness testing and data analysis; developing strength and power; motor skill acquisition and development; strategies for competition priming; monitoring training load, fatigue and recovery. Advanced Strength and Conditioning: an evidence-based approach is a valuable resource for all advanced students and practitioners of strength and conditioning and fitness training
The strength and conditioning scientist / Perry Stewart, Paul Comfort and Anthony Turner -- Developing strength and power / Tim Suchomel, Paul Comfort and Michael Stone -- Stretch-shortening cycle and muscle tendon stiffness / John McMahon -- Endocrinology and resistance training / Anthony Turner and Christian Cook -- Training aerobic fitness / Alex Bliss and Rob Harley -- Repeat sprint ability and the role of high intensity interval training / Anthony Turner and David Bishop -- Concurrent training / Richard Clarke, Roigo Aspe and Jonathan Hughes -- Periodisation / Anthony Turner and Paul Comfort -- Monitoring training load, fatigue and recovery / Tim Gabbett -- Strategies for pre-training and competition priming / Mark Russell, Natalie Williams and Liam Kilduff -- Strategies to enhance athlete recovery / Emma Cockburn and Phil Bell -- Fitness testing and data analysis / John McMahon, Paul Comfort and Anthony Turner -- Movement analysis and corrective exercise / Chris Bishop -- Technical demands of strength training / Tim Suchomel, John McMahon and Paul Comfort -- Weightlifting for sports performance / Tim Suchomel and Paul Comfort -- Demands of plyometric training / Chris Sole -- Training change of direction and agility / Sophia Nimphius -- Speed and aceleration training / Peo Jimenez-Reyes, Bret Contreras and Jean-Benoît Morin -- Applied coaching science / Nick Winkelman.
Includes bibliographical references and index
Keywords: Muscle strength; Physical education and training; Physical fitness -- Physiological aspects